Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/jxb/erp352
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in concentrations, xylem and phloem flows, and partitioning of elements and ions in intact plants. A summary and statistical re-evaluation of modelling experiments in Ricinus communis

Abstract: Within the last two decades, a series of papers have dealt with the effects of nutrition and nutrient deficiency, as well as salt stress, on the long-distance transport and partitioning of nutrients in castor bean. Flows in xylem and phloem were modelled according to an empirically-based modelling technique that permits additional quantification of the uptake and incorporation into plant organs. In the present paper these data were statistically re-evaluated, and new correlations are presented. Numerous relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 134 publications
(245 reference statements)
3
75
0
1
Order By: Relevance
“…9, B and C), indicating that xylem-to-phloem transfer mediated by NRT1.11 and NRT1.12 for nitrate redistribution in leaves is important for high-nitrate-enhanced shoot growth. The amino acid concentrations in the phloem sap can be 30 to 100 times higher than that of nitrate (Allen and Smith, 1986;Hayashi and Chino, 1986;Shelp, 1987;Peuke, 2010). Although nitrate is not the major nitrogen in the phloem, the growth phenotype of nrt1.11 nrt1.12 double mutants suggested that phloem-mediated nitrate redistribution is not dispensable, and compared with amino acid, nitrate may have additional effects on young leaf growth as a signaling molecule, osmoticum, and/or regulator of redox stasis.…”
Section: Nrt111 and Nrt112 Are Important For High-nitrate-enhancedmentioning
confidence: 99%
“…9, B and C), indicating that xylem-to-phloem transfer mediated by NRT1.11 and NRT1.12 for nitrate redistribution in leaves is important for high-nitrate-enhanced shoot growth. The amino acid concentrations in the phloem sap can be 30 to 100 times higher than that of nitrate (Allen and Smith, 1986;Hayashi and Chino, 1986;Shelp, 1987;Peuke, 2010). Although nitrate is not the major nitrogen in the phloem, the growth phenotype of nrt1.11 nrt1.12 double mutants suggested that phloem-mediated nitrate redistribution is not dispensable, and compared with amino acid, nitrate may have additional effects on young leaf growth as a signaling molecule, osmoticum, and/or regulator of redox stasis.…”
Section: Nrt111 and Nrt112 Are Important For High-nitrate-enhancedmentioning
confidence: 99%
“…The nitrogen status of the plant regulates genes coding for nitrate transporters and N-assimilatory enzymes at transcriptional, translational and post-translational levels [276] [277]. Expression of nitrogen assimilatory genes nitrate reductase, nitrite reductase, glutamate synthase and carbon metabolism genes are induced by nitrate [136] [278]- [283]. Assimilation of one molecule of 3 NO − generates 0.67 molecule of OH − which is effluxes into the soil from the roots.…”
Section: Translocation and Assimilation Of Nitratementioning
confidence: 99%
“…From these data, xylem and phloem fluxes as well as total net uptake by the root can be estimated for the whole lifetime of the plant [summarised, e.g. by Peuke (2010)]. A critical point is that the composition of vascular saps may be highly variable with time and data just represented a-somewhat arbitrary-snapshot, whereas the nutrient content of root and shoot tissue has evolved over the whole lifetime of that plant.…”
Section: Sapflow Measurements Based On Local Heatingmentioning
confidence: 99%